2022
DOI: 10.1002/tox.23530
|View full text |Cite
|
Sign up to set email alerts
|

Role of N6‐methyladenosine RNA modification in the imbalanced inflammatory homeostasis of arsenic‐induced skin lesions

Abstract: This study aimed to investigate the effect of N6-methyladenosine (m 6 A) modification in modulating inflammatory homeostasis of arsenic (As)-induced skin lesions. Our bioinformatic analysis revealed abnormal expression of m 6 A RNA methylation regulators and cytokines in the arsenic-exposed population. In human keratinocytes, arsenite increased the levels of m 6 A methylation by upregulating the RNA methyltransferase like 3 (METTL3), mediating the disordered secretion of indicators that reflect inflammatory ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Further experiments found that arsenic promoted m 6 A methylation by up-regulating METTL3 to increase the secretion of inflammatory factors including interleukin-(IL-) 6, IL-17, and IL-10 in human keratinocytes. Keratin 1 (KRT1) and keratin 10 (KRT10) reflecting skin injury were also significantly increased [34]. Another study demonstrated that METTL14 facilitated global genome repair (GGR) by regulating m 6 A RNA methylation-mediated DNA damage-binding protein 2 (DDB2) translation and inhibits ultraviolet B-(UVB-) induced skin tumorigenesis.…”
Section: Roles Of M 6 a Methylation In Skin Tumorsmentioning
confidence: 99%
“…Further experiments found that arsenic promoted m 6 A methylation by up-regulating METTL3 to increase the secretion of inflammatory factors including interleukin-(IL-) 6, IL-17, and IL-10 in human keratinocytes. Keratin 1 (KRT1) and keratin 10 (KRT10) reflecting skin injury were also significantly increased [34]. Another study demonstrated that METTL14 facilitated global genome repair (GGR) by regulating m 6 A RNA methylation-mediated DNA damage-binding protein 2 (DDB2) translation and inhibits ultraviolet B-(UVB-) induced skin tumorigenesis.…”
Section: Roles Of M 6 a Methylation In Skin Tumorsmentioning
confidence: 99%
“…In regard to anti-inflammatory factors, m 6 A can modulate cytokines through the regulation of the p38 and MAPK inflammatory signalling pathways under METTL3 modification. Elevated METTL3 in human keratinocytes specifically regulates inflammatory responses by upregulating m 6 A levels to induce increased secretion of the anti-inflammatory cytokine IL-10 [105] . Given that anti-inflammatory cytokines can interact with proinflammatory cytokines to influence the SASP-induced inflammatory response and cellular senescence [ 106 , 107 ] , there is some evidence of a potential role for m 6 A in cellular senescence by targeting the production of pro- and anti-inflammatory factors.…”
Section: Regulatory Role Of M 6 a In Cellular Sene...mentioning
confidence: 99%